2014
DOI: 10.1002/14651858.cd001367.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Duration of treatment with vitamin K antagonists in symptomatic venous thromboembolism

Abstract: Analysis 2.1. Comparison 2 Long vs short, period a er cessation of study medication until end of follow-up, Outcome 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…Conversely, in patients with TTR≥65% the risk of stroke/SE did not show a trend over time but the risk of major bleeding was highest in the third 4-month period. The latter finding confirms a previous publication reporting an increase of bleeding over time in patients with venous thromboembolism who are anticoagulated with VKA [19]. The authors compared major bleeding in patients with prolonged and short treatment and found major bleeding rates of 2.4% and 0.9%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, in patients with TTR≥65% the risk of stroke/SE did not show a trend over time but the risk of major bleeding was highest in the third 4-month period. The latter finding confirms a previous publication reporting an increase of bleeding over time in patients with venous thromboembolism who are anticoagulated with VKA [19]. The authors compared major bleeding in patients with prolonged and short treatment and found major bleeding rates of 2.4% and 0.9%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Among heart transplant patients, the incidence rate of VTE recurrence has been shown to be 30.5 (95% CI 13.2–60.2) episodes per 1000 patient‐years, mostly in patients in whom oral anticoagulation had been completed . While treatment with warfarin post‐VTE has been shown to strongly reduce the VTE recurrence rate, it is not associated with reduction in mortality and an elevated risk for major bleeding remains . There is evidence to show that continuation of low‐dose aspirin following completion of anticoagulant therapy reduces the rate of VTE recurrence without increased risk of major bleed .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K antagonists (VKAs), delivered with a short period of parenteral anticoagulation [unfractionated heparin (UFH), low molecular weight heparin (LMWH), or fondaparinux] over the first 5-10 days, are recognized as the standard of treatment for VTE, being associated with a VTE recurrence risk of *3 % while patients are on treatment [2].…”
Section: Introductionmentioning
confidence: 99%